Opinion Mining in Facebook Regional Discussion Groups: A Case Study to Identify Health, Education and Security Posts in Discussion Groups - Sápiras, Leonardo Augusto; Weber, Rodrigo Antônio (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2019)
This paper presents the results a case study that apply opinion mining about health, security and education, using as source discussions in Facebook regional groups. The method used is quite different from other researches because it propose an approach to identify regional posts. Five different supervisioned learning algorithms was applied during the classification step. The results show that region's posts can be identified with this new approach.